Fourteen Pedagogical Principles Arising From the Three-Dimensional Paradigm (TDP) of the New Humanism - Sánchez Sánchez, Juan Diego (2020)
The article conducts a theoretical and hermeneutic analysis based on a literature review that addresses the individual’s neural behavior. The cerebral hemispheres, the theory of the three brains, the synaptic processes, and neuro-motivation, linked to the person’s behavior, are the aspects studied. These aspects allow structuring the theoretical foundations and support the concept of neuro-behavior. Later, an exegesis linked to the general concepts of neuro-economics is conducted, where the individuals’ neural behavior is analyzed. The analysis is performed from the two main economic approaches: the left and the right ones, from which the concept of neuro-demand is structured. Finally, based on the analysis done, a mathematical and graphic model of neuro-economic demand management and its respective equation is proposed.